272 Clinical Audit on Transient Ischaemic Attack Investigations in Acute Medical Unit. (16th September 2019) - Karpinski, Sylvia; Collins, Orla; Kelly, Emer; Therese Cooney, Mary; McGrath, Emett
Abstract: Background: TIA (Transient Ischaemic Attack) is a transient episode of neurologic dysfunction. Patients with a TIA have a high early risk of recurrent stroke. These patients need urgent initial evaluation with brain imaging, neurovascular imaging and cardiac evaluation. We conducted retrospective audit in our Acute Medical Unit (AMU) to assess waiting time and type of investigations completed as per TIA guidelines Methods: All consecutive admissions with suspected TIAs were evaluated on length of stay, type of imaging tests obtained and how long they awaited for these tests. This was assessed by reviewing discharge summaries, and times and dates of scans on hospital imaging system. Results: There was a total of 28 patients admitted to AMU with suspected TIA's. Of these, 16 were female and 12 were male. Mean age was 70. All patients had CT brain done on admission, two out of 28 had to wait more than 12 hours. 25 out of 28 (89%) patients got US Carotid Dopplers, and two had CT intracranial angiograms. Average waiting time for US Carotid Dopplers was 33 hours, shortest wait was 6 hours and longest was 72 hours. 14 out of 24 (58%) had inpatient heart monitoring (24h telemetry or 24h Holter) two were excluded with known atrial fibrillation, one had PPM in situ and one refused monitoring. Average length of stay in AMU was 3 days. Conclusion: Patients admitted to AMU with suspected TIAs had relevant imaging and tests completed as per guidelines. 89 % had US Carotid Dopplers which were on average done 33h from admission. 58% of patients had inpatient heart monitoring. The average length of stay was 3 days but three patients stayed in AMU for up to 5 days. Protected imaging slots for AMU would expedite investigations and reduce inpatient stay.